Fotografia e arte: Geraldo de Barros e José Oiticica Filho (1950- 1964) - Etcheverry, Carolina Martins (2012)
This thesis is a reflection about the photographies of brazilian artists Geraldo de Barros and José Oiticica Filho, created in the period between 1950 1964. Because of their abstract character, due to the fact that their referent aren t clearly identifiable, these photographies challenge the observer. Concerning the first photographer, we analyze the series Fotoformas exposed at MASP, in 1950. For the second, we analyze his Abstrações, Formas, Ouropretenses, Derivações e Recriaçõesnames chosen by Oiticica Filho himself for his different photographic series. The documentary authority of the photography is questioned by the creation of images opposing the idea of mimesis of reality. We seek to define the concept of abstract photography from various authors, as well as to insert this kind of images in a larger context of visual arts and the history of photography. We use the comparative method, starting from the idea that the images have different temporalities, to think about the denial the formula content over form , achieved by these photographers using experimental techniques.